Perencanaan Laba Perusahaan Farmasi Go Public - Renny Mointi; ady Kurnia (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
The purpose of this study is to analyze differences in the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange. This type of research is descriptive research with a quantitative approach, the data source used is secondary data, namely data in the form of company’s annual financial reports from 2015 - 2019 attached to the IDX website. Data collection techniques in this study use documentation techniques. Research population Pharmaceutical companies listed on the Indonesia Stock Exchange, sampling using purposive sampling method, namely PT. Kalbe Farma Tbk (KLBF) PT. Kimia Farma, (KAEF), and PT. Pharos Tbk (PEHA). The data analysis technique used in this research is the Profitability Ratio Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE) analysis technique, namely 5 periods of financial statements for each of 3 pharmaceutical companies using standard ratio analysis. industry profitability by cashmere. The results showed that the differences in the financial performance of 3 pharmaceutical companies listed on the IDX were seen from the profitability ratio of Net Profit Margin (NPM) for 5 years, namely PT. Kalbe Farma Tbk, PT. Kimia Farma Tbk is not very good and PT. Pharos Indonesia, Tbk is not good enough. Return On Asset (ROA). PT. Kalbe Farma Tbk, PT. Kimia Farma Tbk is not very good and PT. Pharos Indonesia, Tbk is not very good. Return On Equity (ROE) The financial performance of PT. Kalbe Farma Tbk, PT. Kimia Farma Tbk is not very good and PT. Pharos Indonesia, Tbk is not very good.